2016
DOI: 10.1038/srep26928
|View full text |Cite
|
Sign up to set email alerts
|

The novel compound Sul-121 inhibits airway inflammation and hyperresponsiveness in experimental models of chronic obstructive pulmonary disease

Abstract: COPD is characterized by persistent airflow limitation, neutrophilia and oxidative stress from endogenous and exogenous insults. Current COPD therapy involving anticholinergics, β2-adrenoceptor agonists and/or corticosteroids, do not specifically target oxidative stress, nor do they reduce chronic pulmonary inflammation and disease progression in all patients. Here, we explore the effects of Sul-121, a novel compound with anti-oxidative capacity, on hyperresponsiveness (AHR) and inflammation in experimental mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Previously, we demonstrated that 6-chromanol derived SUL-compounds are protective in models of type 2 diabetes 7 , long-term hypothermic storage 5 and chronic obstructive pulmonary disease 8 . Further, the molecular mechanisms of SUL-compounds were studied in detail in adipose-tissue-derived stem cells demonstrating that compound SUL-109 activated mitochondrial membrane complexes I and IV thereby alleviating mitochondrial ROS production and preserving ATP production 5 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, we demonstrated that 6-chromanol derived SUL-compounds are protective in models of type 2 diabetes 7 , long-term hypothermic storage 5 and chronic obstructive pulmonary disease 8 . Further, the molecular mechanisms of SUL-compounds were studied in detail in adipose-tissue-derived stem cells demonstrating that compound SUL-109 activated mitochondrial membrane complexes I and IV thereby alleviating mitochondrial ROS production and preserving ATP production 5 .…”
Section: Discussionmentioning
confidence: 96%
“…In type 2 diabetes, treatment with SUL-121 halted the progression of kidney damage and prevented endothelial dysfunction through a mechanism involving lowered ROS production 7 . Further, in chronic obstructive pulmonary disease, SUL-121 also reduced ROS production, resulting in reduced LPS-induced airway hyper reactivity and neutrophil influx and increased hydrogen sulfide (H 2 S) production 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, COPD treatment options include quitting smoking, pharmacological treatment (short-acting anticholinergic, short-acting beta 2 -agonist, long-acting anticholinergic, long-acting beta 2 -agonist, and inhaled corticosteroids), and nonpharmacological treatment (pulmonary rehabilitation) [ 7 9 ]. Aim of pharmacological treatment is to improve the quality of life and exercise tolerance beside achieving the reduction of symptoms and attacks [ 7 , 8 ]. Inhaled corticosteroids specifically reduce the number of COPD exacerbations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties are influenced by pathophysiological processes, including a variety of pulmonary diseases, thereby increasing the clinical relevance of blood rheology information [ 13 , 15 – 17 ]. In COPD patients, RBC were shown to alter morphologically, like cytoskeleton changes, ultrastructural modifications, and reductions of glycophorin A, band 3, and RBC thiols [ 7 , 18 , 19 ]. Rheological blood properties were demonstrated to progressively deteriorate as pulmonary insufficiency increases in patients with chronic bronchitis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of NOX4 expression was markedly slowing COPD progress by modulating ROS production in ASM [ 9 ]. Sul-121 is a novel compound with anti-oxidative capacity and can effectively inhibit airway inflammation and airway hyperresponsiveness in COPD models by reducing intracellular reactive oxygen species production in ASM [ 55 ]. Leptin receptor increased expressed on ASM of COPD and has be found inhibited ASM proliferation, migration and eotaxin production through stimulating ASM to secrete prostaglandin E2 [ 56 ].…”
Section: Asm In the Development Of Novel Therapeutic Approaches For Cmentioning
confidence: 99%